The answer would be the last option. :)
Answer:
I will assume that the term "x+2/2" is meant to be "(x + 2)/2)." Otherwise the equation would read (x/3) = x + 1
Step-by-step explanation:
(x/3) = (x + 2)/2
x = 3*(x+2)/2 [Multiply both sides by 3]
x = (3x + 6)/2
x = (3/2)x + 6/2
x - (3/2)x = 3
-0.5x = 3
x = -6
====================
Check:
Does (x/3) = (x + 2)/2 for x = -6?
(-6/3) = (-6 + 2)/2
-2 = -4/2
-2 = -2 YES
Answer: (-2, -2)
Step-by-step explanation:
Reflection over the x-axis: (x, y) → (x, -y)
(-2, 2) → (-2, -2)
x would remain the same but the y would turn negative since we're reflecting over the x-axis. The x never changes in this situation but since we're flipping it over the x-axis, they y has to be negative.
Hope this helps!